"It's Parallel Universes". Issue 10 (October 2015) - Haas, Barbara; Gotlib Conn, Lesley; Rubenfeld, Gordon D.; Scales, Damon; Amaral, Andre C.; Ferguson, Niall D.; Nathens, Avery B.
<x xml:space="preserve">Abstract</x> Objectives: The intensivist-led model of ICU care requires surgical consultants and the ICU team to collaborate in the care of ICU patients and to communicate effectively across teams. We sought to characterize communication between intensivists and surgeons and to assess enablers and barriers of effective communication. Design: Qualitative interview study. An inductive data analysis approach was taken. Setting: Seven intensivist-led ICUs in four academic hospitals. Subjects: Surgeons (attendings and residents), intensivists (attendings and residents), and ICU nurses participating in the care of surgical patients in the ICU. Interventions: None. Measurements and Main Results: Communication enablers and barriers existed at two distinct levels: 1) organizational and 2) cultural. At an organizational level, participants identified that formally sanctioned communication structures and processes often acted as barriers to communication. Participants had developed informal strategies to improve communication. At a cultural level, surgical and ICU participants often expressed conflicting perspectives regarding patient ownership, scope of practice, and clinical expertise. Conclusions: Major barriers to optimal communication between surgical and ICU teams exist in the intensivist-led ICU environment. Many are related to the structures and processes meant to facilitate communication across teams and others to how some aspects of care in the ICU are conceptualized. Multiple actionable opportunities exist to improve communication in the intensivist-led ICU.